Optimization Disaster Logistics by Determining the Optimal Location and Number of Evacuation Centers - Syafrianita Syafrianita; Agus Purnomo; Mohamed Ibrahim Abdul Mutalib (Jurnal Manajemen Industri dan Logistik, 2025)
Indonesia, particularly Bandung Regency, faces significant flood risks that disrupt livelihoods and damage infrastructure. This study identifies the optimal locations and number of evacuation centers using the Set Covering Problem (SCP) model, integrating geographic data, population density, accessibility, and infrastructure capacity. The study applied constraints including a 1,000-meter maximum service distance, minimum road width of 6 meters for Class IIIB and IIIC access, shelter capacity limits, and full coverage of demand points. Using ArcGIS 10.2.1, candidate locations were evaluated by overlaying flood vulnerability maps with accessibility and facility data. Environmental sustainability was addressed by selecting sites with minimal ecological disruption, avoiding sensitive zones, and reusing existing structures to reduce land conversion. Results show that five centralized shelters in high-density, well-connected areas can cut evacuation travel time by up to 20% compared to dispersed locations. This integrated approach improves response efficiency, ensures access for vulnerable populations, and supports sustainable site planning. The findings contribute to disaster logistics theory and offer practical, replicable guidance for policy in other flood-prone regions.